Third-party Reimbursement of Pharmacist-Led Cardiovascular and Diabetes Preventive Health Services for Workplace Health Initiatives: A Narrative Systematic Review - Brandon Tong; Anita Kapanen; Jamie Yuen (University of Minnesota Libraries Publishing, 2021)
Objective: To summarize available literature describing third-party payer reimbursement models for pharmacist-led preventive health services as part of workplace health initiatives. Methods: A combination of search terms related to pharmacists, preventive health, and third-party reimbursement were searched in MEDLINE, EMBASE, and PubMed. Included studies described community pharmacist-led cardiovascular and diabetes preventive health service to employees older than 18 years of age as part of a workplace health program with corresponding third-party reimbursement models. Programs that were reimbursed by government resources or studies lacking reimbursement model details were excluded. One reviewer performed level 1 screening and three reviewers analyzed included studies. Results: The search criteria yielded 863 results. Sixteen articles were reviewed after level 1 screening and 13 were ineligible and excluded. Three studies with varying quality of reporting were included. Reimbursement models varied from $40 USD for a 20-minute visit to $391 to $552 USD total per patient with an average of 6 visits per patient. Conclusion: There is a lack of quality literature describing third-party reimbursement models for pharmacist-led preventive health services, which hinders the ability to implement a standardized model. High quality studies evaluating the cost of reimbursing pharmacist-led cardiovascular preventive health services compared to the savings to the third-party payer should be performed to inform the standardization of payment models.